2009
DOI: 10.4161/psb.4.6.8359
|View full text |Cite
|
Sign up to set email alerts
|

Callose synthesis in higher plants

Abstract: Callose is a polysaccharide in the form of β-1,3-glucan with some β-1,6-branches and it exists in the cell walls of a wide variety of higher plants. Callose plays important roles during a variety of processes in plant development and/or in response to multiple biotic and abiotic stresses. It is now generally believed that callose is produced by callose synthases and that it is degraded by β-1,3-glucanases. Despite the importance of callose in plants, we have only recently begun to elucidate the molecular mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
278
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(283 citation statements)
references
References 26 publications
4
278
0
1
Order By: Relevance
“…To test this, we performed immunofluorescence experiments using three representative cell wall antibodies against callose, (1,3;1,4)-b-glucan, and pectin. In developing wild-type subaleurone cells, callose was deposited as dotted structures at the plasmodesmata (Supplemental Figure 6A), as reported previously (Chen and Kim, 2009). In contrast, (1,3;1,4)-b-glucan and pectin were deposited evenly in the cell wall (Supplemental Figures 6C and 6E).…”
Section: Abnormal Deposition Of Callose and Cell Wall Components In Pmbssupporting
confidence: 57%
See 1 more Smart Citation
“…To test this, we performed immunofluorescence experiments using three representative cell wall antibodies against callose, (1,3;1,4)-b-glucan, and pectin. In developing wild-type subaleurone cells, callose was deposited as dotted structures at the plasmodesmata (Supplemental Figure 6A), as reported previously (Chen and Kim, 2009). In contrast, (1,3;1,4)-b-glucan and pectin were deposited evenly in the cell wall (Supplemental Figures 6C and 6E).…”
Section: Abnormal Deposition Of Callose and Cell Wall Components In Pmbssupporting
confidence: 57%
“…It is known that callose synthesis and deposition can be quickly induced by biotic stresses such as plasmolysis in plants (Chen and Kim, 2009). The uploading of mistargeted DV cargos into the apoplast in the gpa3 mutant may represent a physiologically similar process to plasmolysis.…”
Section: Mistargeting Of Dvs To the Pm Leads To Pmb Formationmentioning
confidence: 99%
“…The first subgroup of AtGSLs includes AtGSL1, AtGSL5, AtGSL8, and AtGSL10; the second subgroup contains AtGSL2, AtGSL3, AtGSL6, and AtGSL12; the third subgroup consists of AtGSL7 and AtGSL11; and the fourth subgroup consists of AtGSL4. 12 Most of the GSLs in Arabidopsis have been cloned, and the functions of the corresponding GSLs have been identified. The number of similar studies in rice is limited, only GSL5 has been reported so far (Fig.…”
Section: Gsls In Monocotyledonous and Dicotyledonous Plantsmentioning
confidence: 99%
“…Callose is a natural component of plant cell wall and it is abundant in pollen tubes (Cresti & van Went, 1976). In some situation, its formation can be regarded as a stress response (Chen & Kim, 2009). Our reported fiber structure of callose is unique.…”
Section: Introductionmentioning
confidence: 99%